2021
DOI: 10.3390/horticulturae7080229
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Evolution and Balance of Grape Sugars and Organic Acids in Some New Pathogen-Resistant White Grapevine Varieties

Abstract: Breeding technologies exploiting marker-assisted selection have accelerated the selection of new cross-bred pathogen-resistant grapevine varieties. Several genotypes have been patented and admitted to cultivation; however, while their tolerance to fungal diseases has been the object of several in vitro and field studies, their productive and fruit composition traits during ripening are still poorly explored, especially in warm sites. In this study, five white pathogen-resistant varieties (PRVs) listed as UD 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…Zhang et al [27] showed that among the five varieties of table grapes grown in China, fructose content is slightly higher than glucose and both sugars, accounting for 96.00-98.00% of the total sugar contents in grape berries. Studies also indicate that main sugars of grape berries are fructose and glucose and their ratio was found to be much closer to each other in grape cultivars [28,29]. Sensoy et al [30] and Eyduran et al [25] showed that glucose and fructose content are close to each other in grape cultivars.…”
Section: Sugar Contentmentioning
confidence: 94%
“…Zhang et al [27] showed that among the five varieties of table grapes grown in China, fructose content is slightly higher than glucose and both sugars, accounting for 96.00-98.00% of the total sugar contents in grape berries. Studies also indicate that main sugars of grape berries are fructose and glucose and their ratio was found to be much closer to each other in grape cultivars [28,29]. Sensoy et al [30] and Eyduran et al [25] showed that glucose and fructose content are close to each other in grape cultivars.…”
Section: Sugar Contentmentioning
confidence: 94%
“…Authors described the impact of stress caused by both climate change and human activity resulting in disorder of the optimum temperature (low-and high-temperature stresses), water balance (water and drought stress and irrigation) and the subsequent disturbance of soil parameters. The SI gathers eleven research papers [1][2][3][4][5][6][7][8][9][10][11] and one review [12]. Three papers were dedicated to cold stress, two to salt stress, two to inorganic pollutants such as metals and phosphate (Phi), three to climate change (i.e., high temperature, water and drought stress) and two to irrigation.…”
mentioning
confidence: 99%
“…In the presented SI, the most frequently applied morphological features were: seed germination, plant growth, leaf and berry area, leaf number, stem diameter and plant dry weight [1][2][3]5,[7][8][9][10][11]. Anatomical characteristics were based mainly on the evaluation of epidermis and mesophyll quality and number of cells and chloroplasts [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations